2018
DOI: 10.1021/acsenergylett.8b01698
|View full text |Cite
|
Sign up to set email alerts
|

C(sp3)–H Bond Activation by Perovskite Solar Photocatalyst Cell

Abstract: Inspired by efficient perovskite solar cells, we developed a threecomponent hybrid perovskite-based solar photocatalyst cell, NiO x /FAPbBr 3 /TiO 2 , for C(sp 3 )−H bond activation with high selectivity (∼90%) and high conversion rates (3800 μmol g −1 h −1 ) under ambient conditions. Time-resolved spectroscopy on our photocatalytic cell reveals efficient exciton dissociation and charge separation, where TiO 2 and NiO x serve as the electron-and hole-transporting layers, respectively. The photogenerated charge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
125
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 131 publications
(131 citation statements)
references
References 47 publications
5
125
0
1
Order By: Relevance
“…For instance, Roeffaers et al. developed a three‐component NiO x /FAPbBr 3 /TiO 2 hybrid for the activation of C(sp 3 )−H bonds in toluene or substituted toluenes with high conversion rates (5610 μmol g −1 h −1 ; Figure d) . The introduced TiO 2 and NiO x , acting as the electron‐ and hole‐transporting layers of FAPbBr 3 , respectively, dramatically enhanced the charge‐carrier transfer and photoactivity efficiency (Figure e).…”
Section: Engineering Mhps For Photocatalysissupporting
confidence: 87%
“…For instance, Roeffaers et al. developed a three‐component NiO x /FAPbBr 3 /TiO 2 hybrid for the activation of C(sp 3 )−H bonds in toluene or substituted toluenes with high conversion rates (5610 μmol g −1 h −1 ; Figure d) . The introduced TiO 2 and NiO x , acting as the electron‐ and hole‐transporting layers of FAPbBr 3 , respectively, dramatically enhanced the charge‐carrier transfer and photoactivity efficiency (Figure e).…”
Section: Engineering Mhps For Photocatalysissupporting
confidence: 87%
“…The shells could further facilitate charge carrier transfer via interfacial or band‐alignment engineering across the core–shell structures. Functionalization of the shells with nanoparticles or ligands will enhance the efficiency of solar‐to‐chemical fuel conversion and enable a wide scope of photocatalytic applications (for example organic reactions) beyond water splitting and CO 2 reduction. However, construction of perovskite@shell structures remains challenging, largely because halide perovskite materials are incompatible with the polar solvents that are typically used for shell formation reactions. 2)New protective layers or ligands should be developed for halide perovskites by exploring various coating and growth methodologies.…”
Section: Conclusion and Future Prospectsmentioning
confidence: 99%
“…[102] Entry . [103] They demonstrated that combining the merits of photovoltaics in the photocatalyst architecture improvest he overall performance of such as ystem. At hree-component photocatalyst cell was created for the CÀHf unctionalization of tolueneand cycloalkanes by using FAPbBr 3 perovskite as the main light harvesting material, TiO 2 as the electron transporting layer,a nd NiO x as the hole transporting layer.T his hybrid 2D nanocomposite was first explored in the photo-oxidation of the methyl group in toluenei nw hich an optimal 5wt% NiO x loading onto FAPbBr 3 /TiO 2 was shown to oxidize toluene to benzaldehyde at ar ate of 3800 mmol g À1 h À1 with a selectivity of 86 %f avoring the formation of benzaldehyde over benzylalcohol.…”
Section: Hybridhalide Perovskites For Photocatalytic Organic Synthesismentioning
confidence: 99%